Aging together: Dyadic profiles of older couples' marital quality, psychological well-being, and physical health. (June 2023) - Novak, Josh R; Wilson, Stephanie J; Ermer, Ashley E; Harper, James M
The current study examined couple-level profiles to reveal systematic patterns of health and well-being in older couples. Using latent profile analysis, dyadic profiles were constructed in a national sample of 535 older, different-sex couples based on couples' marital quality, psychological well-being, and physical health. Results revealed 4 distinct profiles: Maritally Satisfied and Healthy (63.5%), Maritally Dissatisfied and Moderately Healthy (14.7%), Maritally Satisfied with Unhealthy Wives (12.3%), and Maritally Satisfied with Unhealthy Husbands (9.3%). Husband age and education, wife education, and marriage length were significant predictors of class membership. Within-class partner concordance analyses confirmed that the latter two profiles featured the largest discordance between partners' health and well-being. Most couples in this sample of older adults belonged to a class who demonstrated successful aging in all domains. A smaller group maintained high marital quality despite physical and psychological difficulties, and other couples were moderately healthy but maritally dissatisfied.